Benthic community structure and geomorphology of uncharted nearshore reefs in Kuantan coastal waters - Kamarudin, Nurazidah; Nik Asbullah, Nik Aisyah Ilnani; Azmi, Amira Nasuha; Mustapa, Mohd Zaini; Mohd. Hanapiah, Muhammad Faiz (Universiti Malaysia Kelantan (UMK), Jeli Campus, 2024)
The nearshore reefs play several important ecosystem functions in marine environments, especially in coastal areas. Six relatively unknown nearshore reef sites were surveyed in the southern Kuantan coastal waters using the coral video transect (CVT) technique between April 2021 and September 2022 to estimate coral reef benthic components. Data analysis on coral reef benthic components indicated that these uncharted nearshore reefs have ‘fair’ coral cover with an average percentage of 39.4 % ± 17.8 in which ST 1 recorded the highest live coral cover coverage with 68.06 %. Abiotic components (sand and rock) were the second-most abundant and the coverage of dead coral was relatively low at all stations. A total of 33 coral genera were recorded in this study in which Porites, Acropora and Montipora mean percentage cover dominated most of the reef sites. Bathymetry data indicated that some of these uncharted reefs were located on submerged shoals with a depth range between 12 – 17 meters. The variation in benthic community composition observed among reef sites highlights the importance of location-specific management and conservation strategies.